Enterprise Risk Management and Earnings Volatility: Investigating the Role of Care Ethics - Desi Adhariani (Australasian Accounting, Business and Finance Journal, 2022)
This study analyzes the impact of the ethics of care implementation, complemented by the effectiveness of enterprise risk management (ERM), on earnings volatility; and to investigate the moderating or mediating role of care ethics in the association. Care ethics emphasizes a good relationship with other stakeholders. This is interpreted in the corporate risk management context with adequate precautionary efforts to mitigate risks. Moreover, the complementary nature of care ethics and ERM implementation has been argued to affect a company’s performance in terms of earnings volatility. Data from a sample of companies listed on the Indonesia Stock Exchange were collected for the period 2012–2016. Quantitative data were analyzed using descriptive statistics and panel regression. From the ethics of care perspective, companies are expected to manage the risks effectively, which is represented in the effectiveness of ERM implementation. The results confirm this proposition, that is, ERM complements care ethics principles applied by a company in alleviating earnings volatility. The additional analysis shows that care ethics strengthens the association between ERM and earnings volatility. ERM is a growing research topic and has been investigated in previous studies. This research complements the previous studies by presenting an alternative, innovative perspective to analyze the effectiveness of ERM in correspondence with the spirit of care ethics.
Keywords: ethics of care; enterprise risk management; earnings volatility; COSO; risk; disclosure